Effect of reinforcement material on impact properties of epoxy - Fadhil, Basim M.; Ahmed, Payman Sahbah; Kamal, Ava Ali (Kurdistan Journal of Applied Research, 2017)
Impact characteristics of Epoxy matrix composites is investigated by impact machine. Four different types of reinforcement are used in the experimental works: type one: 1.9wt% steel fiber, 1.9wt% carbon fiber,1.9 wt% carbon nanotube, 1.9 wt% woven carbon fiber.This work shows that reinforcing epoxy with (1.9 wt% of woven carbon fiber) improves the impact properties where energy, force and deformation values of impact test for this composite were 18.4J, 3580.59 N and 18 mm respectively while for epoxy were 2.927 J, 921.849 N and 18.413 mm respectively.